Survival Analysis in Gastrointestinal Neuroendocrine Carcinoma With Bone Metastasis at Diagnosis - Chen, Genlian; Xu, Qiang; Qian, Shengjun; Wang, Zhan; Wang, Shicheng (Frontiers in Surgery, 2022)
Purpose: Gastrointestinal neuroendocrine carcinoma (NEC) with bone metastasis is rarely reported. The purpose of this study was to explore the prognosis and risk factors of such patients. Patients and Methods: We retrospectively reviewed patients diagnosed as gastrointestinal NECs with bone metastasis at diagnosis from 2010 to 2016 by using the Surveillance, Epidemiology and End Results (SEER) database. Predictors of overall survival (OS) and cancer-specific survival (CSS) were analyzed by univariable and multivariable Cox analysis. Kaplan–Meier plots were draw to show the correlation between independent predictors and survival. Results: A total of 330 gastrointestinal NEC patients with bone metastasis at diagnosis were included for analysis. Over half of patients were male patients and aged over 60 years old. The most common primary site of gastrointestinal NEC with bone metastasis was the pancreas. The prognosis of gastrointestinal NEC with bone metastasis (3-year OS and CSS rates: 16.7% and 17.0%) was very poor. On Cox multivariable analysis, age over 60 years old, no surgery, and lung metastasis were independent predictors of decreased OS and CSS. Conclusions: We identified three independent factors associated with prognosis among gastrointestinal NEC patients with bone metastasis, namely age, surgery, and lung metastasis. For younger gastrointestinal NEC patients with bone metastasis, surgical resection of primary tumors as well as actively treating lung metastasis might be useful for prolonging survival.